Iemanjá no espaço urbano: trabalhos de arte pública enquanto potências na construção das identidades coletivas - Kohler, Milena dos Santos (2023)
The characteristic that sets Public Art apart from other artistic phenomena is its accessibility and availability, which give it great communicative potential and different possibilities for extending the creative process to possible developments in public space. The public factor is essentially related to the human factor and it was based on this fact that the present research was directed towards the social aspects of this area of study, considering the impossibility of separating the work of Public Art from its context of idealization, creation, installation, reception and interaction, the latter two aspects being responsible for its relationship with the community and its collective identity. In developing this work, efforts were directed towards the study of two works conceived in different practices, these being a sculpture and a mural, and through their particularities it was possible to weave relationships between them. Another direction of the research was to find aspects in the works studied that relate to fundamental traits of the collective cultural identity of Espírito Santo and Brazilian identity, such as religious syncretism.